Production Efficiency of Poultry Small-Scale Laying Hen in Indonesia - Nyak Ilham; M Maulana; E Gunawan (Indonesian Center for Animal Research and Development (ICARD), 2021)
Competitiveness of layer business was determined by the level of efficiency, which was influenced by the level of technology adoption, production costs, and economy of scale. This study was carried out from April to July aim to analyse the performance of small-scale layer poultry farming. The study site was in the layer production centre, namely in Payakumbuh West Sumatera, Blitar East Java and Sidrap South Sulawesi. Primary data were collected through interviews with 50 farmers and 12 poultry shops at all study sites. Analysis of the efficiency level is using DEA (Data Envelopment Analysis) software and business feasibility using financial analysis. The following were the main research findings: (1) the development of layer farming technology had not been responded well by farmers so that the production level and mortality of chickens were still below standard; (2) relatively, the level of layer poultry farming efficiency in Sidrap and Payakumbuh was better than in Blitar with a value closer to one, where the inefficiency was due to the use of excessive inputs; and (3) small-scale layer poultry farming was financially feasible, where the determining factors were feed and eggs price. The study recommended the need to add both technical service staff from poultry shops and local agricultural extension workers. Feed costs should be reduced by IDR 1,000 in Blitar and IDR 57 di Sidrap per kilogram of eggs produced per period. In addition, an accurate and better allocation of corn for feed was needed to optimise the ratio of feed and egg price optimal.